Urban brands, culture and social division: Creativity, tension and differentiation among middle class consumers. (November 2014) - Bookman, Sonia
This article considers the relationship between urban brands, consumption and socio-spatial division in the city, drawing on recent theoretical developments in the sociology of brands and empirical material from a study of the Exchange District in the city of Winnipeg, Canada. Focusing on the theme of creativity, the article uses interview data to examine how middle class residents, workers and visitors engage with the creative possibilities and cultural consumption the Exchange District brand offers. At stake in this process is not only the surfacing of a particular kind of creative culture and neighborhood, but also the performance and positioning of middle class identities. In this process, creativity is elaborated in contradictory and often unintended ways. Parallel to existing work on authenticity and class, the article argues that different notions and practices of creativity are bound up with tensions between moral and cultural boundaries, constituting horizontal divisions between the middle classes who inhabit this urban space.